Itararé Group Sandstone as a Sustainable Alternative Material for Photon Radiation Shielding - Gabrielli W. Pietralla; Isonel S. Meneguzzo; Luiz F. Pires (Applied Sciences, 2025)
The materials typically used for radiation shielding include lead, concrete, and polymers. However, some of these materials can be toxic or very expensive to produce. This raises interest in using more readily available natural materials, such as rocks, as an alternative. In this study, we analyzed the radiation shielding efficiency of sandstones. We evaluated different layers of rock and obtained shielding parameters based on the composition of various oxides. The analysis revealed that these layers showed a predominance of silicon and aluminum oxides. Notably, the lowest photon energies (0.015 MeV and 0.1 MeV) displayed significant differences in photon attenuation, as indicated by linear and mass attenuation coefficients. This suggests that the chemical composition of the samples had a considerable impact on their shielding performance. Samples containing higher amounts of heavier elements proved to be more effective at attenuating radiation, efficiently reducing 50% (half-value layer) and 90% (tenth-value layer) of the photons. Additionally, the presence of these heavier elements decreased the production of secondary photons (buildup factor), further enhancing the samples’ efficiency in shielding against radiation. Our results indicate that sandstones hold potential for radiation shielding, particularly when they contain higher quantities of heavier elements.